Pengaruh Motivasi Kerja Dan Promosi Jabatan Terhadap Kinerja Pegawai Di Sekretariat Dprd Kabupaten Lampung Barat - Gunanto, Gunanto; Junaidi, Junaidi (Jurnal Bisnis, Manajemen dan Akuntansi, 2025)
Improving the quality of work of government officials is aimed at supporting the state administration system in carrying out government administration functions, development functions and community service functions. Provisions of Peraturan Pemerintah Number 101 of 2000 about Pendidikan dan Pelatihan Jabatan Pegawai Negeri Sipil, namely increasing knowledge, skills and attitudes to be able to carry out structural position duties professionally based on the personality and ethics of Civil Servants (PNS) in accordance with the needs of their agency. The government seeks to improve the performance of its agencies in several ways, one of which is by creating a conducive employee promotion mechanism to foster high motivation to display their best performance. Job promotion is the process of moving an employee from one position to another, higher position. Job promotion is the process of moving an employee from one position to another, higher position. The aim of this research is to determine: 1. Work motivation on employee performance 2. The influence of position promotion on employee performance 3. The influence of work motivation and position promotion together on employee performance at the West Lampung Regency DPRD Secretariat. This research uses a quantitative descriptive research method, namely a research method that uses data in the form of numbers to analyze the facts found which aims to determine the relationship between variables in a population. The analysis used is simple and multiple regression. This research used 35 respondents. Based on the results of data analysis, the hypothesis answer was found as follows; There is an influence of Work Motivation (X1) on Performance (Y) at the West Lampung Regency DPRD Secretariat, with a level of influence (R-square) of 72.5%. There is an influence of Position Promotion on Performance at the West Lampung Regency DPRD Secretariat with an influence level of 62.2%. There is an influence of Work Motivation and Position Promotion together on employee performance at the West Lampung Regency DPRD Secretariat, with an influence level of 75.4%